Coherent control of Goos-Hänchen shift in a guided-wave surface plasmon resonance structure with Rydberg atoms - Dingyu Cai; Mengmeng Luo; Yuetao Chen; Shaoyan Gao (Results in Optics, 2021)
We proposed an effective and flexible scheme to achieve tunable giant Goos-Hänchen (GH) shift of reflected light in the configuration of guided-wave surface plasmon resonance with Rydberg atoms. With the super atom model of Rydberg atom due to the dipole blocking effect, we investigated the influence of Rydberg state population on GH displacement. By adjusting the external driving field on Rydberg atoms without changing the structure geometry, not only can GH shift be enhanced significantly to the magnitude of millimeter, but also the transition between positive and negative GH shift can be controlled at the same resonant angles. Furthermore, the resonant angle position of the maximum GH shift is also tunable via detuning the field. Our scheme may offer promising prospects for the optical switches and nano-sensors with high precision.